Kemampuan Menulis Recount Text dengan Menggunakan Teknik Picture Series pada Kelas VIII di SMP Negeri 3 Baubau - Sahidin Sahidin (Jurnal Akademik FKIP Unidayan, 2019)
This study aimed at finding out whether the use of picture series technique can improve students writing skill of recount text or not. The subject of this research was 31 students of class VIII SMPN 3 Baubau. This was a classroom action research involving four steps in each cycles, they are planning, action, observation, and reflection. The instruments of this research were test, observation, questionnaires and documentations. The data analysis was presented in the table and chart of progressive analysis, and also in descriptive explanation. The result of quantitative analysis showed that using of picture series can improve students writing skill of the eight grade student of SMP Negeri 3 Baubau. It can be seen from the result of the students’ writing tests and the student‘s involvement which increased continuously during the application of the techniques. The mean score of students was 70.22 before techniques applied as the indications that this score categorized into a insufficient level. After having treatment in the first cycles, the student‘s mean sco improved to 75.15 which categorized into a sufficient level. In the second cycles, the student‘s mean score54 which improved was categorized good to level.79. This improvement was supported by qualitative data.